Impact of caveolin-1 expression on prognosis of pancreatic ductal adenocarcinoma - Suzuoki, M (Nature Publishing Group, 2002)
Caveolin-1 is a major component of caveolae and plays a regulatory role in several signalling pathways. Caveolin-1 was recently identified as a metastasis-related gene in prostate cancer. The clinical effects of caveolin-1 expression in pancreatic carcinoma, however, remain unknown. In this study, we have investigated the relationship between caveolin-1 expression and the clinicopathologic variables and clinical outcome in 79 patients with pancreatic adenocarcinoma undergoing surgical resection. Caveolin-1 expression was determined by immunohistochemistry, using a polyclonal anti-caveolin-1 antibody. Patients were divided into two groups based on the extent of caveolin-1 expression: a negative expression group (immunoreactivity in less than 50% of cells) and a positive expression group. Positive caveolin-1 immunostaining was detected in 32 cases (40.5% of total), while non-neoplastic ductal epithelium showed little or no staining. Positive caveolin-1 expression was correlated with tumour diameter (P=0.0079), histopathologic grade (P=0.0272) and poor prognosis (P=0.0008). Upon multivariate analysis with Cox's proportional hazards model, positive caveolin-1 expression was shown to be an independent negative predictor for survival (P=0.0358). These results suggest that caveolin-1 overexpression is associated with tumour progression, thereby indicating a poor prognosis for certain patients undergoing surgical resection for pancreatic carcinoma. British Journal of Cancer (2002) 87, 1140–1144. doi:10.1038/sj.bjc.6600619 www.bjcancer.com © 2002 Cancer Research UK